2017
DOI: 10.1088/1361-648x/aa91b6
|View full text |Cite
|
Sign up to set email alerts
|

Ground state properties of 3d metals from self-consistent GW approach

Abstract: The self consistent GW approach (scGW) has been applied to calculate the ground state properties (equilibrium Wigner-Seitz radius S and bulk modulus B) of 3d transition metals Sc, Ti, V, Fe, Co, Ni, and Cu. The approach systematically underestimates S with average relative deviation from the experimental data of about 1% and it overestimates the calculated bulk modulus with relative error of about 25%. It is shown that scGW is superior in accuracy as compared to the local density approximation but it is less a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 48 publications
1
4
0
Order By: Relevance
“…1(d), (e), and (f) in LDA as well. Calculated total magnetic moments in LDA and QSGW are both 2.22 µ B for Fe, in agreement with the experimental value 2.22 µ B [32], in contrast to 2.93 µ B in the fully self-consistent GW method [33]. Our results are consistent with Ref.…”
Section: A Bcc Fesupporting
confidence: 91%
“…1(d), (e), and (f) in LDA as well. Calculated total magnetic moments in LDA and QSGW are both 2.22 µ B for Fe, in agreement with the experimental value 2.22 µ B [32], in contrast to 2.93 µ B in the fully self-consistent GW method [33]. Our results are consistent with Ref.…”
Section: A Bcc Fesupporting
confidence: 91%
“…For weakly correlated materials, most results so far have been obtained within approaches such as MP2 23,24,27,36 and GW [37][38][39] at zero temperature. Only recently, finite-temperature results for solids have started to appear [40][41][42][43] . It was demonstrated that MP2 gaps are wildly inaccurate for materials with band gaps smaller than 6 eV 27 , leading to a breakdown of the band gap estimation for silicon and silicon carbide.…”
Section: Introductionmentioning
confidence: 99%
“…The magnetization per particle (M S V) (2.2 × 10 −20 J/T at 370 K) was used for fitting. Assuming the magnetic moment of Co to be 1.71 μ B /Co (where μ B is the Bohr magneton) 24 and the Wigner-Seitz cell radius of Co ≈ 2.6 a B 25 (where a B is the Bohr radius), the average diameter of Co is approximately 3 nm. Although there is no direct on the microstructure of the ultrathin Co layer currently, ultrathin Co can form an island structure on Au, 26 and its estimated size is reasonably small to show superparamagnetism.…”
Section: Journal Of Applied Physicsmentioning
confidence: 99%